An Insight to the Toxic Effect of Sulfamerazine on Porcine Pancreatic Amylase and Lactate Dehydrogenase Activity: An In Vitro Study - Malla, Avirup; Mukherjee, Koel; Mandal, Mukulika; Mukherjee, Aishwarya; Sur, Runa; Gupta, Suvroma (Current Chemical Biology, 2021)
Background: Sulfamerazine, a sulfonamide, has been routinely used to treat various bacterial infections, namely Pneumonia, Urinary tract infections, Shigellosis, Bronchitis, Prostatitis, and many more. It interferes with the bacterial folic acid biosynthesis, albeit higher eukaryotes are not susceptible to its action due to the inherent absence of this specific pathway. Objective: In spite of its constant use, Sulfamerazine administration evokes serious issues like the development of antibacterial resistance through environmental contamination, although how it affects the eukaryotic system, specifically its target identification, has not been addressed in detail. Methods: The source of the cell line, including when and from where it was obtained. Whether the cell line has recently been authenticated and by what method. Whether the cell line has recently been tested for mycoplasma contamination. Hela Cells are cultured as per the standard method, amylase and lactate dehydrogenase assay are conducted using a standard procedure with a spectrophotometer. Binding thermodynamics and conformational study have been estimated with isothermal titration calorimetry as well as with docking. Results: Experimental observations reveal that Sulfamerazine inhibits porcine pancreatic amylase in a noncompetitive mode (IC50 of 0.96 mM). The binding of the drug to porcine pancreatic amylase is entropy-driven with conformational changes of the protein as indicated by concomitant redshift. It enhances the inhibitory effects of acarbose and cetapin on their in vitro pancreatic amylase activity. It augments lipid peroxidation and promotes lactic acidosis in a dose-dependent manner. Docking studies ensure effective interactions between Sulfamerazine and proteins like lactic dehydrogenase and porcine pancreatic amylase. Conclusion: Detailed study is to be conducted to confirm whether the molecular scaffold of Sulfamerazine might serve as an effective repurposed drug acting as a lead molecule to design antidiabetic drugs of future use. Alternatively, it should be prescribed with caution under specific medical situations like diabetes, cancer and hepatic disorders manifesting lactic acidosis to avoid the crisis.
Keywords: lactic acidosis